E-096 Elective carotid artery stenting for high signal lesions on mr black blood images. (23rd July 2017) - Mori, T; Tanno, Y; Kasakura, S; Yosioka, K; Nakai, N
Abstract : Background: Carotid artery lesions with high signal on MR black-blood (BB) images look at high risk for symptomatic embolic complications following carotid artery stenting (CAS). Purpose: The aim of our study was to investigate the effectiveness of our strategy to prevent symptomatic complications following CAS of MR-BB high-signal lesions. Methods: We included in our study patients who underwent elective CAS of MR-BB high-signal lesions between Jan 2015 and Aug 2016.Symptomatic patients underwent CAS 30 days or later after their ischemic events. We performed transbrachial CAS as following; introducing the Spider filter device distal to BB-high lesionsthrough the MSK-guide (6Fr Simmonds-type super-long sheath), dilatation of lesions with a 3mm-diameter balloon catheter (Shiden) and deployment of CarotidWallstents without post-CAS balloon dilatation. Patients started to take clopidogrel and cilostazol before CAS and continued to do them after CAS. They took Yokukansan (TJ-54, Japanese Kampo) and etizolam or suvorexant during peri-CAS periods. We evaluated symptomatic complications. Results: Twenty-nine patients were analyzed.Their average age was 77 years. They had MR-BB high lesions and their average NASCET stenosis rate of 70%, which were reduced to 34.5% after CAS. Neither symptomatic ischemic complications nor hyperperfusion syndrome occurred during peri-CAS average hospitalization of 4.8 days. Conclusion: Our strategy of elective CAS for MR-BB high-signal lesions was effective in preventing symptomatic complications. Disclosures: T. Mori: 6; C; Royalty, Meditit. Y. Tanno: None. S. Kasakura: None. K. Yosioka: None. N. Nakai: None.